Achilles and the Tortoise: Enlightenment Narratives of Progress and Backwardness - Smyčka , Václav (Dějiny – teorie – kritika, 2015)
The idea of continuous progress of mankind, which appeared in late 18th century in connection with the Enlightenment, went hand in hand with the complementary notion of the backwardness of cultures in earlier stage of development. Some cultures were thus seen as archaic and identified with older ‘epochs of mankind’, while others were seen as especially modern, at the forefront of the virtual vector of progress. This study investigates who and in what way presented these narratives in the enlightened society of the Czech Lands and how these narratives functioned in the ‘backward’ cultures. Using the example of historians, statisticians, and publicly active intellectuals who around 1800 described cultural differences in Central Europe (such as M. A. Voigt, F. A. Pabst, L. Zehnmark, M. A. Gotsch, and F. Kindermann), this study investigates the origins of such narratives of backwardness and their role in the Czech society. The author concludes that the role of ‘backward’ cultures was sometimes actively espoused by their representatives and that this model is based on the adoption of a specific regime of temporality, which itself can be seen as a subject of cultural transfer (i.e., it is a cultural transfer of a model of cultural transfer). This last mentioned aspect is developed in the conclusion, which suggests a hypothetical possibility of emancipation from power asymmetries which follow from the complementary narratives of progress and backwardness.